Permainan Interaktif Sebagai Media Pembelajaran pada Anak Usia Dini - Bela Mayang Sari; Suyadi Suyadi (LP. Ma'arif Janggan Magetan, 2024)
This study aims to provide an overview and explain more clearly about interactive games as a learning medium in Early Childhood. This study uses a literature review research method, which is a research approach that involves the collection, analysis, and synthesis of various literature sources relevant to a particular topic. Applying the method by conducting an in-depth literature review to uncover interactive games as a learning medium in early childhood. The data used was obtained from various sources such as scientific articles, journals, and relevant books, which were accessed through the Google Scholar platform. The analysis was carried out by reviewing and interpreting the results of previous research on interactive games in the context of education. This method focuses on an in-depth exploration of how interactive games can form an optimal learning environment to hone thinking skills in early childhood. The results that have been done in four article manuscripts containing interactive games as a learning medium, the essence of the content of the four articles is really extraordinary because it clearly discusses the advantages and disadvantages of integral games in general as a learning medium. In particular, the difference lies in the explanation of the starting point, the importance of understanding or several stages that can be passed as a learning medium. Ultimately, however, it is up to readers, practitioners and researchers to carefully examine the characteristics of interactive games as a learning medium and make decisions about which interactive games should be chosen for the learning media process.